Global fundraising : how the world is changing the rules of philanthropy - Cagney, Penelope, 1956-; Ross, Bernard, 1953- (Hoboken : Wiley, 2013)
A practical guide to the challenges and successes of global fundraising, written by an international team of highly respected philanthropy professionals and edited by two of the leading nonprofit thinkers, Global Fundraising is the first book to genuinely offer a global overview of philanthropy with an internationalist perspective. As the world becomes more interdependent, and economies struggle, global philanthropy continues to increase. More than that, nonprofits are taking up roles that have traditionally been filled by the government-including social welfare, healthcare, and human.
1. Introduction to global fundraising / Penelope Cagney and Bernard Ross -- Part I. An overview of giving by region -- 2. China / Lu Bo and Nan Fang -- 3. Japan / Masataka Uo -- 4. Latin America / Norma GalafassI -- 5. Western Europe / Chris Carnie -- 6. North America / Penelope Cagney and Andrea MacManus ; with a case study by R.F. Shangraw Jr. -- 7. Australia and New Zealand / Sean Triner -- 8. Central and Eastern Europe / Matt Ide, Mair Bosworth, Anca Zaharia ; with an introduction by Chris Carnie -- 9. Africa / Mike Muchilwa -- 10. Middle East and North Africa (MENA) / Tariq H. Cheema -- 11. Asia / YoungWoo Choi and Usha Menon ; with an introduction by Bernard Ross -- 12. India / Usha Menon and Anup Tiwari -- Part II. Overall topics in giving -- 13. Major donors / Angela Cluff and Paula Guillet de Monthoux -- 14. Globarity: the impact of social media on global solidarity / Marcelo Iñarra Iraegui and Ashley Baldwin -- 15. Innovation: the only competitive advantage / Bernard Ross ; with research from Sudeshna Mukherjee -- 16. The charity giants / Rebecca Mauger.
Includes index.
Online resource; title from PDF title page (Wiley, viewed May 23, 2013).
Keywords: Fund raising; Charities; Globalization; Fund raising; Charities; Globalization; Electronic books